Low serum miR‐19a expression as a novel poor prognostic indicator in multiple myeloma. Issue 8 (19th September 2014) - Hao, Mu; Zang, Meirong; Wendlandt, Erik; Xu, Yan; An, Gang; Gong, Dasen; Li, Fei; Qi, Fang; Zhang, Yanru; Yang, Ye; Zhan, Fenghuang; Qiu, Lugui
<x xml:space="preserve">Abstract</x> Multiple myeloma (MM) is the second most common hematologic malignancy characterized by the clonal expansion of plasma cells. Despite continuing advances, novel biomarkers are needed for diagnosis and prognosis of MM. In our study, we characterized the diagnostic and prognostic potential of circulating microRNAs (miRNAs) in MM. Serum miRNA levels were analyzed in 108 newly diagnosed symptomatic MM patients and 56 healthy donors (HDs). Our analysis identified 95 dysregulated miRNAs in newly diagnosed MM patients. Of the 95 dysregulated miRNAs, dysregulation of miR‐19a, miR‐92a, miR‐214‐3p, miR‐135b‐5p, miR‐4254, miR‐3658 and miR‐33b was confirmed by quantitative reverse transcription PCR (RT‐qPCR). Receiver operating characteristic analysis revealed that a combination of miR‐19a and miR‐4254 can distinguish MM from HD with a sensitivity of 91.7% and specificity of 90.5%. Decreased expression of miR‐19a was positively correlated with international staging system advancement, del(13q14) and 1q21 amplification. Furthermore, downregulation of miR‐19a resulted in significantly decreased progression‐free survival (PFS) and overall survival (OS). Our analysis indicated that the poor prognostic correlation of miR‐19a expression was independent of genetic abnormalities in MM. Multivariate analysis revealed that miR‐19a was a significant predictor of shortened PFS and OS. Interestingly, although miR‐19a levels portend a poor prognosis, patients with low miR‐19a levels had an improved response to bortezomib compared to those with high miR‐19a profile. Patients with downregulated miR‐19a experienced a significantly extended survival upon bortezomib‐based therapy. These data demonstrate that the expression patterns of serum microRNAs are altered in MM, and miR‐19a levels are a valuable prognostic marker to identify high‐risk MM.